Construction of Nontoxigenic Mutants of Nonproteolytic Clostridium botulinum NCTC 11219 by Insertional Mutagenesis and Gene Replacement. - Clauwers, Charlien; Vanoirbeek, Kristof; Laurence Delbrassinne; Michiels, Chris W (Appl Environ Microbiol, 2016)
UNLABELLED: Group II nonproteolytic Clostridium botulinum (gIICb) strains are an important concern for the safety of minimally processed ready-to-eat foods, because they can grow and produce botulinum neurotoxin during refrigerated storage. The principles of control of gIICb by conventional food processing and preservation methods have been well investigated and translated into guidelines for the food industry; in contrast, the effectiveness of emerging processing and preservation techniques has been poorly documented. The reason is that experimental studies with C. botulinum are cumbersome because of biosafety and biosecurity concerns. In the present work, we report the construction of two nontoxigenic derivatives of the type E gIICb strain NCTC 11219. In the first strain, the botulinum toxin gene (bont/E) was insertionally inactivated with a retargeted intron using the ClosTron system. In the second strain, bont/E was exchanged for an erythromycin resistance gene using a new gene replacement strategy that makes use of pyrE as a bidirectional selection marker. Growth under optimal and stressed conditions, sporulation efficiency, and spore heat resistance of the mutants were unaltered, except for small differences in spore heat resistance at 70°C and in growth at 2.3% NaCl. The mutants described in this work provide a safe alternative for basic research as well as for food challenge and process validation studies with gIICb. In addition, this work expands the clostridial genetic toolbox with a new gene replacement method that can be applied to replace any gene in gIICb and other clostridia. IMPORTANCE: The nontoxigenic mutants described in this work provide a safe alternative for basic research as well as for food challenge and process validation studies with psychrotrophic Clostridium botulinum In addition, this work expands the clostridial genetic toolbox with a new gene replacement method that can be applied to replace any gene in clostridia.
Keywords: Botulinum Toxins; Clostridium botulinum type E; Gene Deletion; Hazard Analysis and Critical Control Points; Hot Temperature; Mutagenesis, Insertional; Recombination, Genetic; Sodium Chloride; Spores, Bacterial